Pervasive Decision Support Systems in Healthcare Using Intelligent Robots in Social Media - Taha SAMAD-SOLTANI; Peyman REZAEI-HACHESU; Marjan GHAZISAEEDI (Tehran University of Medical Sciences, 2017)
Please provide alternate text for this image to ensure accessibility for users with text-only browsers or assistive devices.